Influence of thickness size in sheet metal forming - Bressan J.D.* (2008)
A new approach on the influence of sheet thickness and material plastic properties on the limit strains in thin sheet metal forming is developed, using the strain gradient model that predict the local necking onset from initial thickness imperfections. As a result of the analysis, the definition of a roughness concept parameter is presented: the initial roughness profile inclination to thickness ratio parameter. Also, the critical normalized strain gradient at the onset of local necking can be calculated from the initial assumed roughness profile. A brief review of stretch forming of sheet metal, the diagrams and the limiting strain curves for local necking, FLC, and the limit strain theories are presented. The main characteristics of the sheet metal forming processes are also identified and are based in the press shop practice. The limit strains for different thickness sizes are obtained using the present model and a numerical code developed by the author. Present theoretical model produced reasonable predictions about the influence of thickness size on the FLC. © Springer/ESAFORM 2008.